Her beauty and her terror: A case study exploring the framing of water and extreme water events within formal education in Queensland, Australia and Saskatchewan, Canada. (November 2016) - Sammel, Ali
Abstract: The existence of freshwater is fundamental to all life on the planet. Water and society constantly shape and reshape each other. Historically and contemporarily, freshwater exists in dialectical relationship with societies. Despite this, most people seem to have an inadequate understanding of water. To explore this problem, this paper investigates how the concept of 'water' is constructed through the discursive practice of formal education in Queensland, Australia and Saskatchewan, Canada. A review of formal education curricula was chosen because schooling integrates students into a knowledge community focused on defined social and cultural knowledge. In other words, formal education shapes how individuals, communities and societies make sense of water. This analysis shows that water is constructed as a predominantly nature-based phenomenon and offered decontextualized. Understandings of extreme water events are virtually non-existent. This paper concludes with recommendations for future curriculum development, specifically ensuring that what is taught and how it is taught directly relates to the lives of the students and their community.